Optimizing the Role and Function of the Regional Supervisory Board Against the Abuse of Notary Position in Balikpapan City - Aziza, Adela Fitri; Darmadi, Nanang Sri (Jurnal Konstatering, 2025)
Abstract. The examination conducted by the MPD on notaries in Balikpapan City has not been optimal so that the MPD cannot directly monitor and supervise documents issued by notaries or other notary protocols and the MPD is concerned that there are still notaries who make mistakes related to the abuse of notary office and the notary code of ethics. The purpose of this study is to determine and analyze the role and function of MPD supervision of the abuse of notary office in Balikpapan City which has not been optimal and to determine and analyze the optimization of the role and function of MPD supervision of the abuse of notary office in Balikpapan City. The approach method in this study is the empirical legal method. The research specifications used are Structural approach research and Economic Analysis of Law. The type of data uses primary data and secondary data. Theory of the Working of Law and Structural Theory and functionalism. The results of the research and discussion in this study are: The role and function of MPD supervision of abuse of office by Notaries in Balikpapan City in practice still faces various challenges both in the examination at any time (periodically) or when there are reports from the public resulting in the ineffectiveness of the MPD's role, further supervision in principle MPD Balikpapan City is not a superbody, but as a mentor, protector and protector and tries to accompany Notaries, including the status of Notaries who are summoned to be examined as witnesses and in such cases of course there must be a basis for determining the Notary concerned as a witness. Because the Notary who is summoned does not mean or is not necessarily guilty, but there could be other factors that cause the Notary concerned to have the status of a witness who may also be a suspect. For this reason, improvements are needed that start from within, namely the institution that appoints and the Notary organization itself. In this case, the role of the organization is needed so that the problem does not drag on because it will harm the Notary himself which will ultimately also harm the community, so that to solve this problem there needs to be a commitment from all parties who are competent in this matter. Keywords: Examinations; Function; Notary; Optimization.